Hydrogen pickup during oxidation in aqueous environments: The role of nano-pores and nano-pipes in zirconium oxide films - Hu, J; Liu, J; Lozano-Perez, S; Grovenor, CRM; Christensen, M; Wolf, W; Wimmer, E; Mader, EV (Elsevier, 2019)
Oxidation of metals by water generates hydrogen which can enter the solid causing serious degradation of its mechanical properties and may also influence the corrosion rate. The present work focuses on hydrogen pickup during the corrosion of zirconium alloys in an aqueous environment. Transmission electron microscopy using Fresnel imaging on three different samples of oxidized Zr has been used to study the type, distribution, concentration and connectivity of nano-porosity as a function of depth through the oxide layer. Extensive interconnected nano-pipes are found in the non-protective outer part of the oxide, while in the protective barrier layer closer to the metal-oxide interface, continuous nano-pipes turn into individual nano-pores. Ab initio calculations show that molecular hydrogen is formed spontaneously by the reaction of water with oxygen vacancies in zirconium oxide. Molecular dynamics simulations reveal that these H2 molecules can diffuse rapidly through nano-pores and nano-pipes as small as 0.5 nm in the oxide layer. Calculations demonstrate that molecular hydrogen dissociates spontaneously on surfaces of suboxides found experimentally at the metal-oxide interface. Oxygen vacancies in ZrO enable the ingress and diffusion of H atoms with an energy barrier of approximately 65 kJ/mol. Further diffusion of hydrogen through oxygen-saturated α-Zr metal is fast, leading to the formation of thermodynamically stable zirconium hydrides. Thus, formation and diffusion of molecular hydrogen through nano-pores in the bulk oxide and ingress of H atoms via suboxides is a possible mechanism of hydrogen pickup in any metal or alloy covered by an oxide scale that contains nano-porosity.